Effect of various encapsulating agents on the beads' morphology and the viability of cells during BB-12 encapsulation through extrusion. (April 2021) - Frakolaki, Georgia; Giannou, Virginia; Topakas, Evangelos; Tzia, Constantina
Abstract: The present work implements the encapsulation of the probiotic strain Bifidobacterium animalis subsp. lactis (BB-12) in various encapsulating mixtures through extrusion. The surface morphology of the beads produced, as well as the survival of the probiotics' cells was evaluated during storage at 4 °C and −18 °C, and throughout the in vitro simulation of the gastrointestinal system. The results demonstrated that the combination of alginate with nanocrystalline cellulose, whey or carrageenan enhanced the viability of BB-12 in all cases. The incorporation of glycose into the mixture increased the survival rates by 12.9 up to 42.2% during refrigerated storage. The best results were achieved through the replacement of water by milk, maintaining the bacterial count above 6 logcfu/g during storage at 4 °C and −18 °C for 4 weeks. By using milk, the highest survival rates during the in vitro simulation of the gastrointestinal system were also provided (up to 81.2%). Highlights: Encapsulating mixtures were successful matrices for the maintenance of BB-12 viability. Milk beads provided great improvement of BB-12 viability during storage. Glycose addition in the encapsulating blend offers significant viability increase. High survival rates during in vitro simulation of GI tract, up to 83.7%.